Potensi Citicoline sebagai Terapi Neuroproteksi dan Neuroregenerasi pada Stroke Iskemik Akut - Kanilla, Zalfa Nihamuyassari; Azizah, Maryam; Sari, Fery Luvita (PT Kalbe Farma Tbk., 2024)
Ischemic stroke, caused by a blockage in the brain’s blood vessels, is a critical emergency that requires immediate treatment. This study examined the efficacy of citicoline as an adjunct therapy to improve outcomes in acute ischemic stroke. A comprehensive search of four databases (Cochrane Library, ScienceDirect, PubMed, and Google Scholar) was conducted, identifying a total of 5265 articles. Three clinical trials were selected for critical appraisal. Agarwal demonstrated a larger reduction in stroke infarct volume in the citicoline group (4.22 cm3) compared to the placebo group (2.63 cm3) (p=0.483). On day 90, the citicoline group exhibited superior results in mRS scores of 0-2 (p=0.732), NIHSS scores of 0-2 (p=0.934), Barthel index ≥95 (p=0.564), and patient mortality (p=0.468). Seifaddini’s study revealed improved peak systolic velocity and mean arterial flow velocity in the cerebrovascular system. Enrico’s study showed improved mean short afferent latency inhibition in the cholinergic circuits of the citicoline group (p=0.004). Citicoline proves effective as an adjuvant neuroprotective and neuroregenerative therapy for acute ischemic stroke.